Reading comprehension processes in fourth and fifth grade children - Soler Arias, Edibelcy; Escobar Alba, María Cristina; Agudelo Arias, Mirtha Lorena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present qualitative study was carried out during the years 2015 and 2016 at the “Granada Occidente” and “San Antonio Bajo” branches of the “San Rafael” Agricultural Educational Institution in Rondón (Boyacá, Colombia); Its purpose is to determine the processes of reading comprehension that are strengthened by the implementation of strategies designed based on conceptual pedagogy and the “theory of the six readings” by Miguel de Zubiría Samper, the target population consists of eight children of the fourth and fifth grades of primary school between 10 and 11 years old, the collection of information is done through the application of interview, observation and the preparation of checklists; Five workshops are applied with five categories in mind: phonetic reading, primary decoding, secondary decoding, tertiary decoding and categorial reading. The results allow to find progress in half of the children in secondary decoding evidencing faults in the extraction of sentences contained in the sentences; the other half have advanced to tertiary coding level.